2019
DOI: 10.1002/pi.5826
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antifouling activities of fluorinated polyurethanes

Abstract: A series of fluorinated polyurethanes (FPUs) with various contents of fluorinated chain extender (EF) and the same amount of poly(oxytetramethylene glycol) and diphenylmethanediisocyanate were synthesized to explore the relationship between the surface physicochemical properties and bulk microphase separation structures of these FPUs and their antifouling activities against model bacteria and platelets. The bulk microphase separation of FPUs increased with the amount of incorporated EF. It was found that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…5 Surface energy is a measuring criteria for settlement of fouling species which is also related to surface wettability. 6,7 Adhesion effect related to surface energy has been studied by employing widely different materials of high energy (epoxides and urethanes) to low energy (silicones and fluorinated materials). 8 Yandi et al demonstrated antialgal behavior of settlement of zoospore and growth of sporal assays of marine algae Ulva lactuca and Ulva linza by the positively charged poly(2-(dimethylamino) ethyl methacrylates) (PDMAEMA) brushes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Surface energy is a measuring criteria for settlement of fouling species which is also related to surface wettability. 6,7 Adhesion effect related to surface energy has been studied by employing widely different materials of high energy (epoxides and urethanes) to low energy (silicones and fluorinated materials). 8 Yandi et al demonstrated antialgal behavior of settlement of zoospore and growth of sporal assays of marine algae Ulva lactuca and Ulva linza by the positively charged poly(2-(dimethylamino) ethyl methacrylates) (PDMAEMA) brushes.…”
Section: Introductionmentioning
confidence: 99%
“…Strength of attachment depends upon the chemistry of the material that describes the strength of adhesion 5 . Surface energy is a measuring criteria for settlement of fouling species which is also related to surface wettability 6,7 . Adhesion effect related to surface energy has been studied by employing widely different materials of high energy (epoxides and urethanes) to low energy (silicones and fluorinated materials) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Microbial growth can be inhibited by different types of materials like nanocomposite, polymer composites, and polymeric systems [5]. Among these materials, polymer-based systems are the best antimicrobial materials and have numerous advantages over conventional materials with exceptional film-forming ability, suitable chemical activity, thermal stability, mechanical strength, corrosion resistance, and low cost [6]. Various antifouling polymer systems were developed to exhibit increased efficiency, enhanced antimicrobial behavior, process ability, tunable properties, low toxicity, prolonged life time, and diverse functionalities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al synthesized a novel fluorinated diol 3‐(bis‐(N,N‐dihydroxyethyl))dodecafluoroheptyl acrylate (DEFA) via Michael addition reaction between diethanolamine and dodecafluoroheptyl acrylate and manufactured the waterborne polyurethane. Luo et al fabricated the fluorinated chain extender of N‐(1,3‐dihydroxypropan‐2‐yl)‐2,2,3,3,4,4,5,5,6,6,7,7,7‐tridecafluoroheptanamide and prepared a series of different FPU, which displayed excellent antifouling activities against both model bacteria and blood platelets . In addition, latex film formed by waterborne polyurethane is of water/organic solvent resistance thermal stability and mechanical properties .…”
Section: Introductionmentioning
confidence: 99%